(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The article examines the interpretation of the fantasy genre in the works of Ursula Le Guin. Ursula Le Guin’s works are analyzed and compared in terms of changes in the system of images of literary sources. Fantasy, in particular, is characterized by such features as the transfer of internal conflict to the external plane, the shift of emphasis from the personal changes of the characters to their adventures, and the change of the hero’s journey based on the story.